Performa Mesin Sepeda Motor Empat Langkah Berbahan Bakar Premium dan Pertamax - FX. Sukidjo (Forum Teknik, 2011)
The Republic of Indonesian government proposes the owners of  private vehicle in order to use pertamax as fuel. Premium will be consumpted specially for the  public transportation. Therefore it is required research how the effect of fuel used to the engine performance.      This research has used a matic motor cycle engine as testing material. This vehicle is used because matic vehicle are large applicated as private transportation. Data which are required as performance of the engine, involve power and torsion, rate of fuel consumption, temperature of cylinder head cover and emission of the axhausted gas.     Based on the anaysis of the data, can be concluded that type of the fuel affects to the engine which consumpted pertamax are higher than engine which consumpted premium. Rate of premium consumption is larger than rate of pertamax consumptionKeywords : engine performance, oil fuel, emision.